Electro-absorption modulation in GeSn alloys for wide-spectrum mid-infrared applications - Yun-Da Hsieh (Nature Portfolio, 2021)
Silicon-based electronic-photonic integrated circuits are promising for various applications, but their mid-infrared optical modulation is elusive. Here, tunable mid-infrared electro-absorption modulation, with broadband operation range >140 nm, is achieved in GeSn alloys on Si by controlling the Sn content.